2017
DOI: 10.1186/s12884-017-1428-z
|View full text |Cite
|
Sign up to set email alerts
|

Women’s satisfaction with intrapartum care in St Paul’s Hospital Millennium Medical College Addis Ababa Ethiopia: a cross sectional study

Abstract: BackgroundSatisfaction during intrapartum care is the most influential attribute on maternal health service return behaviors and utilization. Measuring satisfaction of women with intrapartum care helps to address the problems and improves the quality of delivery services. The aim of this study is to assess women’s level of satisfaction during intrapartum care.MethodA hospital based, analytic, cross sectional study was conducted at St. Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa Ethiopia, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 16 publications
3
31
7
Order By: Relevance
“…This study revealed variables like: gestational age at birth, duration of stay, mode of transportation (use of free Ambulance), fetal outcome, status of pregnancy and pain managements were predictor's of delivery service satisfaction among study participants. This finding is consistent with other studies conducted at different part of Ethiopia [10,12,28,29]. Likewise, Mothers who gave birth at preterm and full term were less satisfied than those who gave birth at post term (AOR: 0.027, 95% CI: 0.003-0.25), AOR: 0.067, 95% CI: 0.01-0.40) respectively.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study revealed variables like: gestational age at birth, duration of stay, mode of transportation (use of free Ambulance), fetal outcome, status of pregnancy and pain managements were predictor's of delivery service satisfaction among study participants. This finding is consistent with other studies conducted at different part of Ethiopia [10,12,28,29]. Likewise, Mothers who gave birth at preterm and full term were less satisfied than those who gave birth at post term (AOR: 0.027, 95% CI: 0.003-0.25), AOR: 0.067, 95% CI: 0.01-0.40) respectively.…”
Section: Discussionsupporting
confidence: 90%
“…However, the findings of this study is higher than the studies done in western Nepal, Northern Jordan, Kenya, Felege Hiwot Referral hospital (Ethiopia) and St.paulose hospital (Ethiopia) which were 67.8%, 64%, 56%, 74.9% and 19% respectively [8,[10][11][12]18]. This variation may be due to difference back ground of the study participants, satisfaction measurement tools used, study time difference, method of analysis.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations